Effect of HDI Components and Development of MSMEs on Economic Growth and Their Implications on Poverty and Unemployment Province of Yogyakarta Special Region (DIY) - Senen Senen; Rudy Bratamanggala; Pudji Astuty (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
The purpose of this study is to identify, review, analyze, discover and describe the Effect of IPM Components and MSME Development on Economic Growth and Their Implications for Poverty and Unemployment in DIY Provinces. The research methods used in this study are quantitative with tiered regression analysis techniques for crossection and time series data. The results showed that in model 1 health, knowledge, real per capita expenditure and the development of UMKM significantly and positively affect the economic growth of DIY Province, health and education variables have a partial impact on economic growth while per capita spending and the development of UMKM partially has no effect on economic growth, in model 2 shows that economic growth is significant and negative. Affecting the poverty of the population of DIY Province, in model 3 shows that economic growth significantly and negatively affects the unemployment of the residents of DIY Provinces.